2005
DOI: 10.1111/j.1744-697x.2005.00028.x
|View full text |Cite
|
Sign up to set email alerts
|

Alpine grassland degradation and its control in the source region of the Yangtze and Yellow Rivers, China

Abstract: Serious grassland degradation is endangering the environment of the source regions of the Yangtze and Yellow Rivers (SRYYR). There is an urgent need to analyze and review the grassland resources, status of grassland degradation, factors causing grassland degradation, and measures for grassland protection and restoration so as to ensure sustainable development in the SRYYR. This review shows that: (1) The alpine meadow, one of the most important grassland types in the SRYYR, can be divided into four subtypes: t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
201
1
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 274 publications
(214 citation statements)
references
References 17 publications
(18 reference statements)
4
201
1
1
Order By: Relevance
“…our study also indicates that plant diversity decreases because fewer shrub species and forbs are able to adapt to coarse soil texture and sand burial than herbaceous species (Li 2000) and that reduces water-holding capacity of topsoil, which is unfavourable for the survival of herbaceous species (Shang et al 2006). Desertification of alpine meadow severely reduces vegetation coverage, and biomass of herbaceous plants and monocotyledon species, which are essential feed for livestock decrease, while dicotyledons unsuitable for animal consumption proliferate (Zhou et al 2005). in general, desertification not only decreases plant diversity but also constrains pastoral usage due to the reduction of herbaceous biomass and an increase of unpalatable species.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…our study also indicates that plant diversity decreases because fewer shrub species and forbs are able to adapt to coarse soil texture and sand burial than herbaceous species (Li 2000) and that reduces water-holding capacity of topsoil, which is unfavourable for the survival of herbaceous species (Shang et al 2006). Desertification of alpine meadow severely reduces vegetation coverage, and biomass of herbaceous plants and monocotyledon species, which are essential feed for livestock decrease, while dicotyledons unsuitable for animal consumption proliferate (Zhou et al 2005). in general, desertification not only decreases plant diversity but also constrains pastoral usage due to the reduction of herbaceous biomass and an increase of unpalatable species.…”
Section: Discussionmentioning
confidence: 99%
“…in the process of alpine meadow desertification, the amount of sedges decreases as a proportion of biomass, unpalatable plants gradually invade, and denuded landscapes in grasslands become obvious due to low vegetation cover, which increases the possibility of wind erosion. at this time, rodents frequently damage vegetation by excessive excavating and gnawing, and wind erosion impacts appear (Zhou et al 2005). These observations are in agreement with results from alpine steppe desertification in QinhaiTibet Plateau .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, numerous studies have indicated that overgrazing is one of the most important causal factors (Green, 1989;Zhou et al, 2002;Christensen et al, 2004;Zhou et al, 2005). Grazing by herbivores can substantially influence the dynamics of plant communities by altering primary production, decomposition of organic matter (OM), the cycling and distribution of nutrients and competitive relationships among plant species (McNaughton, 1985;Fahnestock and Detling, 1999).…”
Section: Introductionmentioning
confidence: 99%